Enjoying Sad Music: Paradox or Parallel Processes? - Schubert, Emery (Frontiers in Human Neuroscience, 2016)
Enjoyment of negative emotions in music is seen by many as a paradox. This paper argues that the paradox exists because it is difficult to view the process that generates enjoyment as being part of the the same system that also generates the subjective negative feeling. Compensation theories explain the paradox as the compensation of a negative emotion by the concomitant presence of one or more positive emotions. But compensation brings us no closer to explaining the paradox because it does not explain how experiencing sadness itself is enjoyed. The solution proposed is that an emotion is determined by two critical processes—labelled motivational action tendency (MAT) and subjective feeling (SF). For many emotions the two processes are coupled in valence. For example, happiness has positive MAT and positive SF, annoyance has negative MAT and negative SF. However, in an aesthetic context, such as listening to music, emotion processes can become decoupled. Sadness retains its negative SF but the aversive, negative MAT is inhibited, leaving sadness to still be experienced as a negative valanced emotion, while contributing to the overall positive MAT. Individual differences, mood and previous experiences mediate the degree to which the aversive aspects of MAT are inhibited. The reason for hesitancy in considering or testing this parallel processes hypothesis, as well as the preponderance of research on sadness at the exclusion of other negative emotions, are discussed.